Karrikin Improves Osmotic and Salt Stress Tolerance via the Regulation of the Redox Homeostasis in the Oil Plant Sapium sebiferum - Shah, Faheem Afzal; Wei, Xiao; Wang, Qiaojian; Liu, Wenbo; Wang, Dongdong; Yao, Yuanyuan; Hu, Hao; Chen, Xue; Huang, Shengwei; Hou, Jinyan; Lu, Ruiju; Liu, Chenghong; et al. (Frontiers in Plant Science, 2020)
Karrikins are reported to stimulate seed germination, regulate seedling growth, and increase the seedling vigor in abiotic stress conditions in plants. Nevertheless, how karrikins alleviate abiotic stress remains largely elusive. In this study, we found that karrikin (KAR1) could significantly alleviate both drought and salt stress in the important oil plant Sapium sebiferum. KAR1 supplementation in growth medium at a nanomolar (nM) concentration was enough to recover seed germination under salt and osmotic stress conditions. One nanomolar of KAR1 improved seedling biomass, increased the taproot length, and increased the number of lateral roots under abiotic stresses, suggesting that KAR1 is a potent alleviator of abiotic stresses in plants. Under abiotic stresses, KAR1-treated seedlings had a higher activity of the key antioxidative enzymes, such as superoxide dismutase, peroxidase, catalase, and ascorbate peroxidase, in comparison with the control, which leads to a lower level of hydrogen peroxide, malondialdehyde, and electrolyte leakage. Moreover, the metabolome analysis showed that KAR1 treatment significantly increased the level of organic acids and amino acids, which played important roles in redox homeostasis under stresses, suggesting that karrikins might alleviate abiotic stresses via the regulation of redox homeostasis. Under abiotic stresses, applications of karrikins did not increase the endogenous abscisic acid level but altered the expression of several ABA signaling genes, such as SNF1-RELATED PROTEIN KINASE2.3, SNF1-RELATED PROTEIN KINASE2.6, ABI3, and ABI5, suggesting potential interactions between karrikins and ABA signaling in the stress responses. Conclusively, we not only provided the physiological and molecular evidence to clarify the mechanism of karrikins in the regulation of stress adaptation in S. sebiferum but also showed the potential value of karrikins in agricultural practices, which will lay a foundation for further studies about the role of karrikins in abiotic stress alleviation in plants.